Synthesis And Characterization Of Chlorine-Free Polycyclotriphosphazene As Adhesive For Glass - Ponnusamy, Rajeswary (2009)

(untitled)
Perekat berasaskan polimer fosfazena tanpa halogen telah disintesis melalui dua langkah yang berlainan.